Sweated Industries and Sweated Labor : The London Clothing Trades, 1860-1914 - Thwaites, James (Relations Industrielles / Industrial Relations, 1986)
This article reviews the book, "Sweated Industries and Sweated Labor : The London Clothing Trades, 1860-1914," by James A. Schmiechen.

Organization Theory : A Macro Perspective for Managing; Organization Theory : Integrating Structure and Behavior - Thwaites, James (Relations Industrielles / Industrial Relations, 1986)
This article reviews the books, "Organization Theory : A Macro Perspective for Managing," by John H. Jackson, Cyrill P. Morgan, and J.G.P. Prolillo, and "Organization Theory : Integrating Structure and Behavior, by Garry Dessler.